ANALYSIS OF VIBRATION CHARACTERISTICS OF SHEARER CUTTING UNIT - XIE Miao; YAN JiangLong; MAO Jun; MIAO LiYe; DONG XianRui (Jixie qiangdu)
The shearer is under complex impact when it works. and it makes the shearer cutting unit vibrate,which increase the burden of the spiral drum and rocker arm shell. Besides,it would bring bad effects to the shear performance of the shearer. In order to study its study the working stability,the vibration mathematical equations in vertical direction and horizontal direction was established by lumped parameter modeling method and solved by the software of MATLAB. And acquire the vibration characteristics when working in different angles of time and frequency domain. The 3D model of the shear cutting unit was established by rigid and flexible coupling method. By the dynamic simulation and analysis from the software of ANSYS and ADAMS,the dynamic response of the shear cutting unit was acquired. The study provide a new method for the analysis of the dynamic response and basis to improve the design and stability of the shear cutting unit.